2021
DOI: 10.3390/cancers13133123
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Alterations in Relation to Histopathological Characteristics in a Large Series of Pediatric Papillary Thyroid Carcinoma from a Single Institution

Abstract: Papillary thyroid carcinoma (PTC) presents distinct clinico-pathological and molecular differences in children compared with adult patients. Whether the presence of rearrangements or point mutations is associated with aggressive PTC clinical presentation is still controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…It has been reported that CPTCs were less represented in patients aged less than 15 years than in patients aged 15-18 years, while FVPTCs occurred more frequently in the former group ( 20 ). However, our results showed that the proportion of CPTCs was higher than that of FVPTCs, both in children aged ≤18 years and in young children aged 2-16 years regardless of with or without DM.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been reported that CPTCs were less represented in patients aged less than 15 years than in patients aged 15-18 years, while FVPTCs occurred more frequently in the former group ( 20 ). However, our results showed that the proportion of CPTCs was higher than that of FVPTCs, both in children aged ≤18 years and in young children aged 2-16 years regardless of with or without DM.…”
Section: Discussionmentioning
confidence: 97%
“…Within the pediatric group under 18 years of age, special attention should be paid to male patients under 15 years old, as they are associated with a more advanced disease at diagnosis ( 5 ). Tumors were generally infiltrative in patients younger than 15 years ( 20 ). Therefore, we believe that it is necessary to take the age into consideration to divide young children separately from adolescents during the development and disease progression of PTC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, gene mutations were found to play important roles in thyroid cancer progression and development [ 27 ]. Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We discuss the THADA gene (also called thyroid adenoma-associated protein) separately, located on the short arm 2p21 of chromosome 2, first discovered in thyroid tumors ( Rippe et al, 2003 ). THADA encodes a thyroid adenoma-related protein in the thyroid, pancreas, and other tissues ( Ling, 2020 ; Castillo-Higuera et al, 2021 ; Macerola et al, 2021 ), which is related to energy metabolism disorders. In this study, we found that the missense and amplification of this gene in the IS3 subtype were significantly lower than the other two subtypes, and its expression was consistent with a better prognostic trend.…”
Section: Discussionmentioning
confidence: 99%